(3HMQ GdCfSGHs - (3GHf YfHI , CMeO Hf Ydj Hf MSjf GdOGhOj GdWGdHj GdMSfj, LeGd GdOjf CHh GdYHGS,J (B828 (3g` s
(3ChdgG (B:s
(3gPG , CJe Gddg fYeg Ydjc, eGSCdJfjg ai EedGA eNJUQ ai CfSGH Hfi gGTe GdcQGe s
(3BNQgG (B:s
(3hEP hab Gddg SHMGfg dEJeGe gPG GdeNJUQ MSHeG hYOfGg adfbWY GdcdGe MGeOjf ddg QH GdYGdejf s
(3YdjgG NW GdYdGeI GdRHjOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B6s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B199 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B272 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B59 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B39) s
Keywords: (3GdJGQjNs